University of Toronto Instructors’ Experiences with Developing MOOCs - Najafi, Hedieh; Rolheiser, Carol; Harrison, Laurie; Håklev, Stian (International Review of Research in Open and Distributed Learning, 2015)
We interviewed eight University of Toronto (U of T) instructors who have offered MOOCs on Coursera or EdX between 2012 and 2014 to understand their motivation for MOOC instruction, their experience developing and teaching MOOCs, and their perceptions of the implications of MOOC instruction on their teaching and research practices. Through inductive analysis, we gleaned common motivations for MOOC development, including expanding public access to high quality learning resources, showcasing U of T teaching practices, and attempting to engage MOOC learners in application of concepts learned, even in the face of constraints that may inhibit active learning in MOOC contexts. MOOC design and delivery was a team effort with ample emphasis on planning and clarity. Instructors valued U of T instructional support in promoting systematic MOOC design and facilitating technical issues related to MOOC platforms. The evolution of MOOC support at U of T grew from a focus on addressing technical issues, to instructional design of MOOCs driven, first, by desired learning outcomes. Findings include changes in teaching practices of the MOOC instructors as they revised pedagogical practices in their credit courses by increasing opportunities for active learning and using MOOC resources to subsequently flip their classrooms. This study addresses the paucity of research on faculty experiences with developing MOOCs, which can subsequently inform the design of new forms of MOOC-like initiatives to increase public access to high quality learning resources, including those available through U of T.